Relationship of changes in physical fitness and anthropometric characteristics over one season, biological maturity status and injury risk in elite youth ski racers: A prospective study - Steidl-Müller, L.; Hildebrandt, C.; Müller, E.; Raschner, C. (International Journal of Environmental Research and Public Health, 2020)
Alpine ski racing is a sport with a high risk of injuries. In order to contribute to the longitudinal career development of young athletes, prevention measures should be elaborated. Therefore, the aim of the present study was to investigate prospectively the role of biological maturity status, and changes in anthropometric characteristics and physical fitness parameters over one season in elite youth ski racers younger than 15 years. Eighty-nine elite youth ski racers (39 females, 50 males), aged 10-14 years (mean age: 12.1 ± 1.3), were investigated. Anthropometric characteristics and physical fitness parameters were assessed prior and after the winter season; traumatic and overuse injuries were recorded over the 32 weeks. Binary logistic regression analyses (R² = 0.202-0.188) revealed that the biological maturity (Wald = 4.818; p = 0.028), and changes over the season in the jump agility test (Wald = 4.692; p = 0.03), in body height (Wald = 6.229; p = 0.013), and in leg length (Wald = 4.321; p = 0.038) represented significant injury risk factors. Athletes who could improve their jump agility performance more, had smaller changes in the anthropometric characteristics and who were closer to their peak height velocity were at a lower injury risk. In the context of injury prevention, regular neuromuscular training should be incorporated, and phases of rapid growth have to be considered.